Functional Interaction Between GABAergic Neurons in the Ventral Tegmental Area and Serotonergic Neurons in the Dorsal Raphe Nucleus - Rahaman, Sheikh Mizanur; Chowdhury, Srikanta; Mukai, Yasutaka; Ono, Daisuke; Yamaguchi, Hiroshi; Yamanaka, Akihiro (Frontiers in Neuroscience, 2022)
GABAergic neurons in the ventral tegmental area (VTA) have brain-wide projections and are involved in multiple behavioral and physiological functions. Here, we revealed the responsiveness of Gad67+ neurons in VTA (VTAGad67+) to various neurotransmitters involved in the regulation of sleep/wakefulness by slice patch clamp recording. Among the substances tested, a cholinergic agonist activated, but serotonin, dopamine and histamine inhibited these neurons. Dense VTAGad67+ neuronal projections were observed in brain areas regulating sleep/wakefulness, including the central amygdala (CeA), dorsal raphe nucleus (DRN) and locus coeruleus (LC). Using a combination of electrophysiology and optogenetic studies, we showed that VTAGad67+ neurons inhibited all neurons recorded in the DRN, but did not inhibit randomly recorded neurons in the CeA and LC. Further examination revealed that the serotonergic neurons in the DRN (DRN5-HT) were monosynaptically innervated and inhibited by VTAGad67+ neurons. All recorded DRN5-HT neurons received inhibitory input from VTAGad67+ neurons, while only one quarter of them received inhibitory input from local GABAergic neurons. Gad67+ neurons in the DRN (DRNGad67+) also received monosynaptic inhibitory input from VTAGad67+ neurons. Taken together, we found that VTAGad67+ neurons were integrated in many inputs, and their output inhibits DRN5-HT neurons, which may regulate physiological functions including sleep/wakefulness.